The use of artificial intelligence in research and education in light of Saudi Arabia’s Vision 2030 “Usage and Challenges” - Bilal, Doha Adel; Al-Zahrani, Maha Abdullah Saeed; Youssef, Yasmin Alaa El-din Ali; Algahtany, Wadha Misfer; Alsherbini, Ola Azmi; Alzahab, Nibras Abo (Research Journal in Advanced Humanities, 2025)
This study explores the current applications of Artificial Intelligence (AI) in Saudi universities and research institutions, emphasizing its role in enhancing educational outcomes and research productivity. Using a theoretical analytical approach, the research examines literature and national strategies to assess AI integration in light of Vision 2030. Supported by initiatives like SDAIA, AI adoption is increasingly essential. Nevertheless, challenges such as data privacy, ethical concerns, faculty readiness, and infrastructure limitations continue to hinder full implementation.